PERAN FINANCIAL TECHNOLOGY DALAM MENINGKATKAN KUALITAS LAYANAN PADA PERBANKAN SYARIAH DI INDONESIA - Nur Ainia, Risna (Jurnal Al-fatih Global Mulia, 2025)
Financial Technology (fintech) is one of the main drivers of innovation in the financial services system, creating new opportunities to improve efficiency, accessibility, and customer satisfaction. This study aims to analyze the role of fintech in improving the quality of Islamic banking services, as well as to evaluate the extent to which the integration of this technology is in line with Islamic principles. The research method used is a qualitative approach with literature studies and secondary data analysis from various related publications. The results of the study indicate that the implementation of fintech, such as Islamic mobile banking, digital payment services, and Islamic-based peer-to-peer financing, has made a positive contribution to increasing the speed of service, transparency, and customer convenience.